2019
DOI: 10.7150/thno.30422
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay for monitoring the anti-aging effect of cord blood treatment

Abstract: Background: Treating aged animals with plasma of an early developmental stage (e.g, umbilical cord plasma) showed an impressive potential to slow age-associated degradation of neuronal and cognitive functions. Translating such findings to clinical realities, however, requires effective ways for assessing treatment efficacy; ideal methods should be minimally invasive, amenable for serial assays, cost-effective, and quantitative.Methods: We developed a new biosensor approach to monitor anti-aging therapy. We adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Interestingly, it has been shown that stress is the main elicitor of TNTs (hyperglycemia, acidified medium, endotoxin, serum starvation, H 2 O 2 , cytokines), similar to some of the mitochondria–PM interactions described above ( 14 , 15 , 61 ). Although the molecular mechanisms are still poorly understood, Miro1 and p53 have been involved, and importantly, Cx43 has been found critical for electric coupling and mitochondria transfer in a model of lung disease ( 65 , 66 ), or after oxygen/glucose deprivation ( 67 ).…”
Section: Mitochondria Transfer: Tntsmentioning
confidence: 99%
“…Interestingly, it has been shown that stress is the main elicitor of TNTs (hyperglycemia, acidified medium, endotoxin, serum starvation, H 2 O 2 , cytokines), similar to some of the mitochondria–PM interactions described above ( 14 , 15 , 61 ). Although the molecular mechanisms are still poorly understood, Miro1 and p53 have been involved, and importantly, Cx43 has been found critical for electric coupling and mitochondria transfer in a model of lung disease ( 65 , 66 ), or after oxygen/glucose deprivation ( 67 ).…”
Section: Mitochondria Transfer: Tntsmentioning
confidence: 99%